2022
DOI: 10.1038/s41598-022-12471-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of carbapenem-resistant Gram-negative bacterial (CR-GNB) isolates retrieved from hospitalized patients in Bihar, India

Abstract: Carbapenemase-producing clinical isolates are becoming more common over the world, posing a severe public health danger, particularly in developing nations like India. Carbapenem-resistant Gram-negative bacterial (CR-GNB) infection has become a fast-expanding global threat with limited antibiotic choice and significant mortality. This study aimed to highlight the carbapenem-resistance among clinical isolates of hospital admitted patients in Bihar, India. A cross-sectional study was conducted with 101 clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Several studies have shown the possibility of K. pneumoniae carrying more than one carbapenem resistance gene in isolates from China, Singapore, India, Europe, and the Middle East [ 43 , 44 , 45 ]. In this study, all isolates showed the coexistence of at least two carbapenems genes, except for isolates K5 and K21, which produced the bla VIM gene only.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown the possibility of K. pneumoniae carrying more than one carbapenem resistance gene in isolates from China, Singapore, India, Europe, and the Middle East [ 43 , 44 , 45 ]. In this study, all isolates showed the coexistence of at least two carbapenems genes, except for isolates K5 and K21, which produced the bla VIM gene only.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, AgNPs exhibit superior antibacterial action against multi-drug resistant (MDR) Enterobacteriaceae (E. coli and S. typhi) with MIC from 10 -15 μg/ml and disrupts growth with inhibition around 50%-60 % for E. coli and S. typhi respectively as shown in table (4) and as illustrated in figure (3). Moreover, combination of sublethal doses of AgNPs with sub-MIC (½MIC) of aminoglycoside antibiotic (Kanamycin) exhibited substantial synergistic bactericidal effects against multi-drug resistant Enterobacteriaceae with FIC index range 0.21 -0.5 for E. coli and 0.2-0.45 for S. typhi as shown in the table (4). The data in the figure (5) confirmed that AgNPs had 55%-65% inhibitory action on biofilm development for pathogenic bacteria isolated from children with diarrhea.…”
Section: Figure (2): Patient Distribution According To Age Categories...mentioning
confidence: 89%
“…The biofilm production classified as strong, moderate, and weak according to ability of microorganism to developing of the biofilms. About 15% of the E. coli strains developed strong biofilm production and compared to approximately 10% of S. typhi; moreover, moderate biofilm production recorded about 10% and 5% for E. coli and S. typhi respectively as described in figure (4). Bacterial cells were cultivated to produce biofilms and then treated with AgNPs alone or in combination with aminoglycoside antibiotics (Kanamycin) to investigate the synergistic effects.…”
Section: Figure (2): Patient Distribution According To Age Categories...mentioning
confidence: 99%
See 1 more Smart Citation
“…P. aeruginosa can get further resistance by overexpression of AmpC, acquisition of mutations causing AmpC hyperactivity or through modification of the antimicrobial target structures [ 6 ]. In addition, horizontal gene transfer plays an important role, allowing the acquisition of resistance genes towards carbapenems [ 7 ] or quinolones ( qnrB , qnrA , and qnrS ), among others [ 8 ].…”
Section: Introductionmentioning
confidence: 99%